Firewatching - Thomas, Russ, 1975- (Simon & Schuster UK Ltd., 2020)
When financier Gerald Cartwright disappeared from his home six years ago, it was assumed he'd gone on the run from his creditors. But then a skeleton is found bricked up in the cellar of Cartwright's burned-out mansion, and it becomes clear Gerald never left alive. As the sole representative of South Yorkshire's Cold Case Review Unit, Detective Sergeant Adam Tyler is not expected to get results, but he knows this is the case that might finally kick start his floundering career. Luckily, he already has a suspect. Unluckily, that suspect is Cartwright's son, the man Tyler slept with the night before. Keeping his possible conflict-of-interest under wraps, Tyler digs into the case alongside Amina Rabbani, an ambitious young Muslim constable and a fellow outsider seeking to prove herself on the force. Soon their investigation will come up against close-lipped townsfolk, an elderly woman with dementia who's receiving mysterious threats referencing a past she can't remember, and an escalating series of conflagrations set by a troubled soul intent on watching the world burn